Inclusive workplace practices: Understanding disability-assistance animal stereotype-bias signals - Rebecca McPherson; Lucas Wayne Loafman (Organization Management Journal (OMJ), 2023)
Purpose - This study aims to fill a distinct gap in the literature on disability-assistance animals (disability-AAs) and inclusive employment by investigating human resource (HR) practitioners' perceptions of disability-AAs in the staffing process and workplace. HR practitioners play a critical role in accommodation and inclusion, yet their experiences and insights have been largely ignored in prior research. Design/methodology/approach - This study used a phenomenological approach, drawing on signaling theory and employability constructs, to explore insights from 17 HR practitioners' experiences with assistance animals in the workplace. Findings - The potential for unconscious bias in employment practices was found, as well as a significant percentage of practitioners who were unprepared to handle animal accommodations. First, the potential development of a positive stereotype bias suggests all genuine assistance animals are high functioning. Second, the assumption that employees' assistance animal requests for invisible disabilities without previous disclosure are presumed fraudulent until proven valid. Research limitations/implications - As a qualitative study, findings from this study are not generalizable to a larger population but may be transferable to similar employment contexts. Originality/value - This study extends knowledge from previous studies, which focused predominately on insights from disabled individuals, animal trainers and therapists, to the HR practitioner domain in creating a more inclusive work environment. Findings from this study suggest the need to improve education about disability-AAs and the potential for unconscious bias for HR practitioners and hiring managers when accommodating requests, particularly when those assistance animals are not described as high functioning.
Keywords: 650; Bias; Emotional support animal; Human resources; Inclusive practice; Service dog